2014
DOI: 10.1016/j.euroneuro.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent intermittent ethanol exposure diminishes anhedonia during ethanol withdrawal in adulthood

Abstract: Adolescent alcohol use may interfere with neurodevelopment, increasing the likelihood of adult alcohol use disorders (AUDs). We investigated whether adolescent intermittent ethanol (AIE) exposure alters the adult reward response to ethanol. Adolescent rats were administered ethanol once (moderate exposure; Cohort 1) or three times per day (severe exposure; Cohort 2) in a 2 days on/2 days off pattern. In adulthood, subjects responded for electrical stimulation directed at the posterior lateral hypothalamus in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…For example, BECs in the present study (AIE vapor: 200–300 mg/dl) were lower than BECs in our earlier study (AIE gavage: 300–500 mg/dl) [37]. However, others have reported increased risky choice in adulthood after self-administration of ethanol-containing gelatin during adolescence, resulting in much lower BECs [812].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…For example, BECs in the present study (AIE vapor: 200–300 mg/dl) were lower than BECs in our earlier study (AIE gavage: 300–500 mg/dl) [37]. However, others have reported increased risky choice in adulthood after self-administration of ethanol-containing gelatin during adolescence, resulting in much lower BECs [812].…”
Section: Discussioncontrasting
confidence: 78%
“…There is growing evidence that exposure to stressors in adolescence impairs brain development, behavioral responses to drugs and alcohol, and cognitive performance in adulthood [39,40]. Therefore, the stress of ethanol administration via gavage during adolescence may have contributed to the increased risky choice observed in our previous work [37]. On the other hand, adult rats exposed to stress-free voluntary ethanol self-administration throughout adolescence exhibited increased risky choice [812].…”
Section: Discussionmentioning
confidence: 98%
“…Although people may not always experience the full spectrum of the physical signs of oxycodone withdrawal, they still may be inflicted with those unpleasant enough to promote escalation of self-dosing, with the drug obtained either through legitimate or illegitimate channels. ICSS has been proposed as a preclinical model that can be used to model affective-like withdrawal symptoms, because many drugs, including morphine (Schaefer and Michael, 1986;Easterling et al, 2000;Liu and Schulteis, 2004;Altarifi and Negus, 2011;Holtz et al, 2015), nicotine (Epping-Jordan et al, 1998;Cryan et al, 2003;Kenny and Markou, 2005;Igari et al, 2014;Manbeck et al, 2014;Qi et al, 2015), ethanol (Schulteis et al, 1995;Chester et al, 2006;Rylkova et al, 2009;Boutros et al, 2014), and cocaine (Markou and Koob, 1991;Stoker and Markou, 2011), produce decreases in ICSS after either spontaneous or precipitated withdrawal. Furthermore, withdrawal from nicotine and morphine has been associated with decreased ventral tegmental area dopaminergic activity, which correlates with ICSS deficits (Liu and Jin, 2004;Kaufling and Aston-Jones, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AIE may induce the persistence of this adolescent-typical ethanol effect, with AIE reported to enhance some, although not all, measures of ethanol’s rewarding effects when AIE and control animals were tested in adulthood (Alaux-Cantin et al, 2013). Although the measures used vary somewhat from those that have been used to assess ethanol effects on reward processing during adolescence, in recent work assessing sensitivity to ethanol challenge-induced reward enhancements and deficits, AIE also was found to decrease the sensitivity of adults to the reward-impairing effects of ethanol and precipitate in a sub-set of the animals atypical ethanol-induced reward enhancement (Boutros et al, 2014). Effects of AIE on later consumption of ethanol in adulthood are mixed, with adolescent-typical elevations in ethanol consumption (e.g., Doremus et al, 2005) reported under some but not all circumstances after AIE (e.g., see McBride et al, 2005; Gilpin et al, 2012; Alaux-Cantin et al, 2013; Broadwater et al, 2013b); critical variables influencing the impact of AIE on later ethanol intake may be related to the mode of ethanol exposure during adolescence (e.g., experimenter administered vs. self-administered; route of exposure) as well as how intake was assessed in adulthood (home cage or limited access; operant self-administration, etc.…”
Section: Retention Of Adolescent-typical Phenotypes After Aie: Cogmentioning
confidence: 99%